Anishinaabeg Niizh Manitoag: Asha Amaa, We Were Always Here - Nobiss, Jacqueline F., X (Scholars Commons @ Laurier, 2023)
ANISHINAABEG NIIZH MANITOAG: ASHAA A’MAA, WE WERE ALWAYS HERE Abstract This research is an in-depth exposé of Anishinaabeg knowledge surrounding niizh manitoag, two-spirit ways of knowing. General collections of two-spirit writings and contributions in the past thirty years uncovered a noticeable gap in the research around Anishinaabeg's two-spirit knowledge, stories, and teachings. Using Indigenous research paradigms, this knowledge base posits a unique theoretical, conceptual framework identified as an Indigenous Relational Theory. The theory delineates a way of knowing and understanding Anishinaabe niizh manitoag, two-spirit identity. The Indigenous Relational Theory consists of four models, Relational Cultural Model, Relational Identity Model, Relational Decolonization Model, and the Relational A Priori Model. Each model is further broken down with Anishinaabeg, proximal nations and niizh manitoag concepts encapsulated under the cultural model. The Relational Identity Model includes normativity, colonization, and sacred protectionism. Within the third model, the Relational Decolonization Model, concepts of non-interference, personhood and self-determination are included. The Relational A Priori Model is comprised of value-laden Indigenous concepts including dreams and visions, blood memory and ancestral knowledge. Together, the concepts come together to provide one way of seeing two-spirit ways of being through an Anishinaabeg worldview. This collection of knowledge brings forward in-depth insights and Indigenous ways of seeing the world through the perspectives of 6 Indigenous teachers, Elders, knowledge keepers and storytellers. Conversations took place with each of the storytellers over multiple meetings where new conceptual understandings were uncovered. The impassioned contributions highlighted collective cultural knowledge as mino bimaadisiwin, the good life, in recognition of the historical, traditional ways of being. In response to cultural adaptations and identity, the gift of the shapeshifter ...